Die Politik der Habsburger gegenüber den wichtigen ethnischen Gruppen Siebenbürgens - Ungarn, Szekler, Sachsen und Rumänen - und ethnischen Minderheiten (1688-1790) - Marinel Ovidiu Koch – Tufiş (Codrul Cosminului, 2013)
The social policy has been a key component of the Habsburgs’ absolutist policy in Transylvania. An important aspect of social policy was the Viennese Court's position against the main ethnic groups of the Principality – Hungarians, Székelys, Saxons and Romanians - and to some other ethnic minorities. This aspect of social policy is characterized by measures taken by the Habsburgs in forming and strengthening their domination in Transylvania, based on ethnic criteria, and also by the Viennese Court’s actions regarding the use of disagreements between the ethnic groups, or as applicable, regarding the amelioration of these misunderstandings for its own interests.